2004
DOI: 10.1007/s11255-004-0918-x
|View full text |Cite
|
Sign up to set email alerts
|

Penile amputation and emasculation: Hazards of modern agricultural machinery

Abstract: We report a case of 20-year-old farmer with penile amputation and emasculation secondary to crushing injury inflicted by agricultural machinery. His entire penis, scrotum and both the testis had been avulsed after falling onto a rotating axel wheel of an electronically driven thrashing machine. After resuscitation the wound was thoroughly washed with saline, hemostasis achieved and a perineal urethrostomy was made from the remnant urethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dogra PN. et al reported a case of penile amputation and emasculation secondary to crushing injury inflicted by agricultural machinery in their study [9]. Hodonou RK.…”
Section: Discussionmentioning
confidence: 97%
“…Dogra PN. et al reported a case of penile amputation and emasculation secondary to crushing injury inflicted by agricultural machinery in their study [9]. Hodonou RK.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the more common mechanisms include self-mutilation, domestic violence, trauma, and failed circumcision [2,4,6,7]. Less common injuries include boating accidents, animal bites, agricultural machinery accidents among others [8][9][10]. A series of penile amputations in ailand were maliciously performed in the 1970's by wives of unfaithful husbands [11].…”
Section: Discussionmentioning
confidence: 99%